INNOVATING DIGITAL “J-SLATE” IN WRITING REPORT TEXTS - Tiasari, Luky (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Creating a report text using technology in the cyber-based era is so unique, especially for the ninth graders of junior high schools. To support technological activities, J-SLATE (Jostle to Write on the SLATE) is proposed in this paper to guide students in writing report texts consisting of five ways: Sail, Lamp, Acceleration, Tool, and Eyot. Three sequences of the R&D model (Plomp:1997) were used to develop this product. At the end of the research, J-SLATE provides tasks and activities related to basic competence, and it also offers digital games based on the students' needs to explore the students' ideas in creating report texts creatively.